CURRENT MODERN ETIOLOGY OF ANEMIA - Kudratova Z. E.; Isomadinova L. K.; Sirojeddinova S. F.; Tursunova M. E. (International Journal of Innovations in Engineering Research and Technology, 2023)
Anemia is a syndrome of many diseases encountered in the practice of primary care physicians of all specialties. The main manifestations of anemic syndrome are symptoms of hypoxia - increased fatigue, weakness, dizziness, tachycardia, shortness of breath, which are nonspecific and often observed in many chronic diseases. This is often the cause of hypodiagnosis and delayed therapy of this condition, which leads to worsening of the course of the underlying disease and prognosis. Anemic syndrome is diverse in its etiology [1,2].